О нервных элементах плавательного пузыря леща (Abramis brama L.) - Бондаренко, Г.В. (Вестник зоологии, 1970)
Пользовались методом импрегнации по Бильшовскому-Гросс как тотально, так и на срезах. В работе описывается характер нервного сплетения плавательного пузыря леща. В образовании сплетения участвуют нервные пучки разного калибра. В нем много клеточных элементов. Клетки располагаются или диффузно, или в ганглиях. Чувствительные образования представлены ветвистыми рецепторами. Описываются амитотические фигуры ядер нервных клеток. The article deals with the data obtained when studying the nerve elements of the swim bladder in Abramis brama L. from the Cyprinidae family. To Find these elements the Bilshovsky-Gross method of impregnation was used both totally and on slides. The type of the nerve plexus of swim bladder in Abramis brama L. is described. The plexus is formed by nerve bundles of a various calibre. The variability of cellular composition is mentioned. The cells arranged either diffusively or in ganglia. The sensitive formations are presented by the ramosa receptors. The amitotic figures of the nuclei of nerve cells are described.